Transformal - Damianovic, Maia; Würtinger, Werner (Wien : Wiener Secession, 1996)
Ball, Lillian ; Canevari, Paolo ; Cassaro, Franklin ; Davey, Grenville ; French, Christopher ; Hyde, James ; Long, Charles ; Marcaccio, Fabian ; Neto, Ernesto ; Ostendarp, Carl ; Risley, Jack ; Schiess, Adrian ; Szymanski, Carol ; Walde, Martin ; Wiener, Daniel
biog., ind. tent., gr. tent. p. 29-35
Transformal, Wiener Secession, Wien, 22.3. - 25.4.1996
Duits & Engels
kunstcatalogus